THE ROLE OF CITIZENSHIP EDUCATION ON STRENGTHENING NATIONAL ANTHEM OF COMMITMENT TO THE COMMUNITY CHINESE ETHNIC PONTIANAK - Suhaida, Dada (Department of Civic Education, 2015)
One of the problems facing the country today is the commitment of the ebb tide of Chinese ethnic nationality in the community. Through citizenship education is central topic of education has strategic role in strengthening the commitment of anthem for nationality being one of a sense of nationality with replanting efforts to uphold the values of Pancasila and the 1945 constitution, love of country, and Bihineka Tunggal Ika, as spirit delivery and eventually developing national anthem of the spirit of nationality and patriotism in the running of social life, socially, and the country. But for shows this phenomenon of ethnic chinese national anthem of having no commitments to the nation and the state of Indonesia.Keywords: education citizenship, nationalism, the commitment of nationalities, Chinese ethnic